The Role of Digital Government in Activating Sustainable Development - The United Arab Emirates as a Model (Journal of Economic Additions, 2025)
This study aims to explore the topic of digitization, government, and sustainable development, as they are important topics of our time, affecting all sectors and fields in countries and around the world. These topics are the result of a series of changes and developments taking place. Our study also focused on presenting the United Arab Emirates as a model for achieving sustainability and providing various digital services.The study found significant interest from the United Arab Emirates in implementing the Sustainable Development Goals and developing a strategy accordingly. The UAE also ranked 11th globally in the United Nations Digital Government Development Index with a score of 0.9533.Jel Classification Codes: O1, O11
Keywords: Keywords: Government, Digital government, Sustainable development, United Arab Emirates.